O adolescente surdo e suas relações interpessoais e afetivas no contexto escolar - Salazar, Daniela Lúcia (2018)
This research aimed to study the interpersonal and affective relations of the deaf adolescent. This is a qualitative study using the technique of content analysis. The participants were eight deaf adolescents, enrolled in a public school in the Federal District. The data were collected through the field diary; of five observations of two hours each, one per day in the classroom; by the semi-structured individual interview in Libras and filmed. Data analysis was carried out with the help of two programs: Elan, which allows the transcription of video in sign language into Portuguese and MAXQDA to categorize and interpret the data based on the content analysis stages according to Bardin (2011). The categories have been renamed: School organization, which presents two subcategories Contributes to the development of interpersonal relationships and Non-contributes to the development of interpersonal relationships. This first category addressed all the aspects that provide the development of the relationships researched and associated with school organization such as proficiency in Pounds, separate intervals, disregard for the opinion of deaf students, and direct lessons in Pounds. Affectivity, which is the second category, pointed the opinions of deaf adolescents about the aspects considered important for the development of affectivity such as intimacy, friendship, exchange of experiences among others. Interpersonal relations, which presents four deaf and non-deaf, deaf and deaf subcategories; Deaf and Teacher, Deaf and Other Officials. In this third category are named aspects that are associated with each type of relationship and what kind of people are involved. For each relationship, different aspects such as daily contact, touch, confidence, demonstration of affection or disaffection, emotions and communication (communication barrier) were presented. The results point to some aspects that contribute, within the school organization, to the development of interpersonal relations, namely: direct classes in the language of instruction - the Libras; classroom layout because it allows the deaf student to follow everything that happens in the classroom. The study demonstrates that for the development of interpersonal and affective relationships it is necessary to acquire trust, intimacy, friendship, daily contact, communication in Pounds or by written Portuguese and demonstration of emotions, as an example embracing as good and exteriorizing the thought of feeling missing.